Strategi Bisnis Berkelanjutan Pada Usaha Kuliner di Samarinda (Studi Pada Ecologico Café) - Andreana, Angelika Gita; Fourqoniah, Finnah (Universitas Negeri Padang, 2024)
This research aims to determine the sustainable business strategy of Ecologico Café Samarinda with a focus on increasing sales of ecofriendly cafes in Samarinda. This research uses IFAS and EFAS analysis was carried out to compile a SWOT analysis matrix which was then followed by a litmus test and USG analysis to see the most strategic strategy to be carried out. The research results show that Ecologico Café Samarinda applies the green marketing concept with 4P indicators, and must implement growth-oriented strategies to maximize strengths and take advantage of opportunities. This research also identified six strategic issues, of which a campaign to maintain diet in a persuasive and interactive manner through online and offline platforms was the most strategic.